2013
DOI: 10.1089/apc.2013.0099
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing HIV Infection in Primary Care Settings: Missed Opportunities

Abstract: In the United States, 20% of HIV-infected persons are unaware of their diagnosis. Improved application of HIV screening recommendations in healthcare settings may facilitate diagnosis. Clinical patient data and previous healthcare visits were reviewed from medical records of newly diagnosed HIV-infected persons in Durham County, North Carolina, who initiated HIV care at Duke University Medical Center in 2008-2011. Comparisons were made to similar data from 2002-2004 using the Pearson's chi-square test and logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 11 publications
2
33
1
2
Order By: Relevance
“…Late diagnosis has generally been found to be more common among men and older adults in multiple studies in the US, Australia, Europe, and Asia. 13,28,[41][42][43][44][45][46][47][48][49][50][51] Health care providers may be less likely to consider HIV infection in an older adult, and older adults may perceive themselves as at lower risk than younger adults. 51 Rapid disease progression, which would appear as a late diagnosis, has been reported in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Late diagnosis has generally been found to be more common among men and older adults in multiple studies in the US, Australia, Europe, and Asia. 13,28,[41][42][43][44][45][46][47][48][49][50][51] Health care providers may be less likely to consider HIV infection in an older adult, and older adults may perceive themselves as at lower risk than younger adults. 51 Rapid disease progression, which would appear as a late diagnosis, has been reported in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…A study by D. German et al [16] demonstrated that high percentages of non-Hispanic/non-Latino black and younger MSM in Baltimore were unaware of their HIV infections and hypothesized that testing efforts were not adequately reaching these groups. Other studies have demonstrated that opportunities for HIV testing are often missed during health care visits [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, factors such as poor reimbursement for HIV tests, competing health needs, and possible provider biases or comfort level in providing positive results to certain patients have been cited as potential barriers to HIV testing by clinicians [54][55][56]. Thus, even when connected to health care, certain populations are less likely to be offered testing [57,58].…”
Section: Discussionmentioning
confidence: 99%